Expansion strategies for human mesenchymal stromal cells culture under xeno‐free conditions. (30th May 2017) - Tozetti, Patrícia Aparecida; Caruso, Samia Rigotto; Mizukami, Amanda; Fernandes, Taisa Risque; da Silva, Fernanda Borges; Traina, Fabiola; Covas, Dimas Tadeu; Orellana, Maristela Delgado; Swiech, Kamilla
Abstract : Choosing the culture system and culture medium used to produce cells are key steps toward a safe, scalable, and cost‐effective expansion bioprocess for cell therapy purposes. The use of AB human serum (AB HS) as an alternative xeno‐free supplement for mesenchymal stromal cells (MSC) cultivation has increasingly gained relevance due to safety and efficiency aspects. Here we have evaluated different scalable culture systems to produce a meaningful number of umbilical cord matrix‐derived MSC (UCM MSC) using AB HS for culture medium supplementation during expansion and cryopreservation to enable a xeno‐free bioprocess. UCM MSC were cultured in a scalable planar (compact 10‐layer flasks and roller bottles) and 3‐D microcarrier‐based culture systems (spinner flasks and stirred tank bioreactor). Ten layer flasks and roller bottles enabled the production of 2.6 ± 0.6 × 10 4 and 1.4 ± 0.3 × 10 4  cells/cm 2 . UCM MSC‐based microcarrier expansion in the stirred conditions has enabled the production of higher cell densities (5.5–23.0 × 10 4  cells/cm 2 ) when compared to planar systems. Nevertheless, due to the moderate harvesting efficiency attained, (80% for spinner flasks and 46.6% for bioreactor) the total cell number recovered was lower than expected. Cells maintained the functional properties after expansion in all the culture systems evaluated. The cryopreservation of cells (using AB HS) was also successfully carried out. Establishing scalable xeno‐free expansion processes represents an important step toward a GMP compliant large‐scale production platform for MSC‐based clinical applications. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1358–1367, 2017